Elder race - Tchaikovsky, Adrian, 1972- (Tordotcom, 2021)
"Lynesse is the lowly Fourth Daughter of the queen, and always getting in the way. But a demon is terrorizing the land, and now she's an adult (albeit barely) with responsibilities (she tells herself). Although she still gets in the way, she understands that the only way to save her people is to invoke the pact between her family and the Elder sorcerer who has inhabited the local tower for as long as her people have lived here (though none in living memory has approached it). But Elder Nyr isn't a sorcerer, and he is forbidden to help, and his knowledge of science tells him the threat cannot possibly be a demon..."--Back cover.